Spore is a bi-monthly magazine - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Spore is a bi-monthly magazine on agricultural and rural development for African, Caribbean and Pacific (ACP) countries. It is published by the Technical Centre for Agricultural and Rural Development ACP-EU (CTA) in English and French, with a sister...